Relative deprivation, and procedural and distributive justice in National Environmental Policy Act scoping documents - Bustos, John R., Jr., author; Long, Marilee, advisor; Thompson, Jessica, committee member; Champ, Joseph, committee member (Colorado State University. Libraries, 2011)
The U.S. Forest Service often deals with very contentious resource management issues. This contention is wrought by the nature and diversity of people using National Forest system lands. The process for making decisions on the management of these issues is called the National Environmental Policy Act (NEPA). This act describes how decisions will be made and how the public will be involved with these decisions based on the comparison of environmental impacts to alternatives usually developed by Forest Service resource managers before the public input process. The first step in NEPA is called scoping. In many cases this scoping is accomplished by sending a letter out to interested parties, called a scoping letter which describes the proposed action. This study examined NEPA-required scoping using a letter. Participants' attitudes toward the Forest Service and their feelings of justice were measured in reaction to information provided in a scoping letter. Participants were assigned to read one of three scoping letters. One letter provided a proposed action that decreased recreational shooting opportunities by eliminating shooting over a large area of National Forest System lands. The second scoping letter provided a proposed action that increased recreational shooting activities by opening up large areas of National Forest System land to shooting activities. The third scoping letter did not mention any proposed action. This letter described the processes that would be used to decide what the problem was regarding shooting and another process that would be used to decide on solutions to the problem. Participants who received the scoping letter that only provided processes had a more positive attitude toward the Forest Service than participants who received a scoping letter with a proposed action. Participants who received a letter with a proposed action that was not in their favor did not have a significantly more negative attitude toward the Forest Service than those who received a decision that was in their favor. In terms of justice, participants with a negative attitude toward the Forest Service who received a scoping letter with a process did not have significantly different feelings of justice than those who received either letter with a proposed action. Finally, no matter what participant's attitude toward the Forest Service, there was no significant difference in their feelings of justice.